2011
DOI: 10.2134/agronj2010.0320
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Intensity and Nitrogen Fertilization Affect Litter Responses in ‘Tifton 85’ Bermudagrass Pastures: II. Decomposition and Nitrogen Mineralization

Abstract: In many grassland ecosystems, nutrient cycling via plant litter is important for plant growth and persistence. Understanding dynamics of litter decomposition and nutrient release under different management practices is critical to understanding nutrient cycling in grasslands, but this topic has received relatively little attention in C4 grass pastures. The objective of this study was to determine the effects of grazing intensity (defined as postgraze stubble height, SH) and N fertilization on litter decomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 24 publications
7
39
2
2
Order By: Relevance
“…For example, the N-enriched litter lost the highest amount of biomass C (65%) and had significantly higher rate of decomposition in the second (wet) decomposition phase (11%). These findings agree with previous observations (Liu et al, 2011;Lupwayi and Haque, 1999) that N fertilization increases biomass decomposition, but suggest that factors other than litter N concentration accelerate decomposition in N-enriched litter. An example of such a factor is an increase in C lability resulting from N enrichment (Peyraud and Astigarraga, 1998), which is a result of N promoting growth of succulent herbage with a low cell wall content (Waite, 1970).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For example, the N-enriched litter lost the highest amount of biomass C (65%) and had significantly higher rate of decomposition in the second (wet) decomposition phase (11%). These findings agree with previous observations (Liu et al, 2011;Lupwayi and Haque, 1999) that N fertilization increases biomass decomposition, but suggest that factors other than litter N concentration accelerate decomposition in N-enriched litter. An example of such a factor is an increase in C lability resulting from N enrichment (Peyraud and Astigarraga, 1998), which is a result of N promoting growth of succulent herbage with a low cell wall content (Waite, 1970).…”
Section: Discussionsupporting
confidence: 93%
“…Dubeux et al (2006) suggested that higher tissue C:N ratios indicate lower N concentration in tissues rather than changes in C concentrations. The decrease in litter N over the study period contrasted with the findings of several previous studies (Deshmukh, 1985;Dubeux et al, 2006;Hamadi et al, 2000;Liu et al, 2011), which reported increased nitrogen masses over the study period. The 68-75% N and 73-83% P of the initial mass released by the end of our 20-week study were higher than the 20-30% N and 60% P mineralization reported by Dubeux et al (2006) for 18-week incubation in sub-tropical Florida, USA.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…This process can become continuous, since sources of nutrients have varying C:N ratios and lignin contents, releasing nutrients at different rates, i.e., days, weeks, or even years. Different defoliation frequencies and intensities, which influence the formation of new tissues, may also affect C and N cycling due to their effects on the biochemical composition of residues (Parsons & Congdon, 2008), N concentrations in the tissues (Liu et al, 2011), and soil microbial population and diversity (Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The net mineralization after 128 days of incubation was ~ 250 g kg -1 of the total N. Increasing stocking rates and N fertilization levels resulted in faster litter turnover and greater nutrient release. Liu et al (2011b) observed that increasing post-graze stubble height from 8 to 16 cm did not affect litter decomposition in Tifton 85 pastures; however, increasing N fertilization levels from 50 to 250 kg ha -1 yr -1 increased litter decomposition.…”
Section: Nutrient Cycling Via Littermentioning
confidence: 80%